Efficacy of an Inactivated Bacterin Vaccine Against Emerging Streptococcus dysgalactiae in Channel Catfish ( Ictalurus punctatus ) - Brent M. Vuglar; Krishna P. Singha; Craig A. Shoemaker; Benjamin H. Beck; Taylor I. Heckman; Jason W. Abernathy; Julio C. García; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2026)
Lancefield Group C Streptococcus dysgalactiae recently emerged as a catfish pathogen in the US. Reports from hatcheries suggest S. dysgalactiae causes substantial broodfish loss. We aimed to develop a challenge model and evaluate vaccine efficacy against S. dysgalactiae in juvenile channel catfish ( Ictalurus punctatus ). Three S. dysgalactiae (14–1, 14–24 and 14–25) isolates were tested for virulence. Intracoelomic (IC) injection demonstrated S. dysgalactiae 14–1 was the most virulent. Reisolated 14–1 was used to develop a formalin‐killed cell (FKC) vaccine. Catfish (200) were immunized via IC injection of 100 μL FKC with adjuvant (1:1 v/v), and another 200 catfish were sham vaccinated. Five fish from each group were bled for antibody titre every 14 days. At 28 and 56 days post‐vaccination (dpv), subsets of both groups were challenged with S. dysgalactiae via IC injection (200 μL/fish) in triplicate (20 fish/tank). Cumulative percent mortality was significantly ( p S. dysgalactiae bacterin induced humoral immunity and protected juvenile catfish. Future studies are planned to evaluate this bacterin in broodfish.